A compact static birefringent interferometer for the measurement of upper atmospheric winds: concept, design and lab performance - Yan, Tingyu; Langille, Jeffery A.; Ward, William E.; Gault, William A.; Scott, Alan; Bell, Andrew; Touahiri, Driss; Zheng, Sheng-Hai; Zhang, Chunmin (Atmospheric measurement techniques, 2021)
A new compact static wind imaging interferometer, called the Birefringent Doppler Wind Imaging Interferometer (BIDWIN), has been developed for the purpose of observing upper atmospheric winds using suitably isolated airglow emissions. The instrument combines a field-widened birefringent delay plate placed between two crossed Wollaston prisms with an imaging system, waveplates and polarizers to produce four fixed 90∘ phase-stepped images of the interference fringes conjugate to the scene of interest. A four-point algorithm is used to extract line-of-sight Doppler wind measurements across the image of the scene. The arrangement provides a similar throughput to that of a field-widened Michelson interferometer; however, the interferometric component of BIDWIN is smaller, simpler to assemble and less complicated to operate. Consequently, the instrument provides a compact, lightweight and robust alternative that can be constructed and operated with lower cost. In this paper, the instrument concept is presented, and the design and optimization of a prototype version of the instrument are discussed. Characterization of the lab prototype is presented, and the performance of the instrument is examined by applying the instrument to measure a low-velocity two-dimensional Doppler wind field with a high precision (5 m s−1) in the lab.